The Medici effect what elephants and epidemics can teach us about innovation - Johansson, Frans (Tantor Audio, 2017)
Frans Johansson's The Medici Effect shows how breakthrough ideas most often occur when we bring concepts from one field into a new, unfamiliar territory, and offers examples on how we can turn the ideas we discover into path-breaking innovations.
Hard copy version record
Keywords: Technological innovations; Creative thinking; Innovations; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Downloadable audio books; Audiobooks; Livres audio